Description of a new genus, Boucekinus (Hymenoptera: Chalcidoidea: Torymidae), with two new species and a discussion of its placement - Janšta, Petr; Vilímová, Jitka; Hanson, Paul (Zootaxa, 2011)
Boucekinus gen. nov. and two new species, B. masneri sp. nov. from Ecuador and B. tatianae sp. nov. from Costa Rica, are described; B. tatianae is designated as the type species. Boucekinus tatianae was reared from cecidomyiid galls on Anemopaegma chrysoleucum (Bignoniaceae) and B. masneri was collected by canopy fogging. The placement of this new genus within Torymidae is discussed.